The impact of government ownership on the cost of debt and valuation of Vietnamese listed companies. Issue 2 (18th March 2020) - Le, Ben
Abstract : Purpose: This paper aims to examine the impact of government ownership on the cost of debt and firm valuation in listed Vietnamese companies for the period 2007 to 2016. Design/methodology/approach: The authors use both the generalised methods of the moment (GMM) and the ordinary least squares (OLS) regressions to analyse a panel data spanning over the period 2007 to 2016 in the markets of Vietnam. Further, the instrumental variable is used in the paper. Findings: The authors find that firms with relative higher government stockholdings or state-owned companies where the government owns 50 per cent or more of shares outstanding enjoy a lower cost of debt compared to the other firms. Consequently, these firms have higher firm valuation and profitability. The results are robust for both the GMM and the OLS regressions. Further, firms that no longer retain government ownership have a higher cost of debt than the other firms. The results of the paper imply the importance of political connections in businesses in the market of Vietnam. Originality/value: This paper connects the relationship between government ownership and the cost of debt with the relationship between government ownership and firm valuation. The paper tests the relationship between the cost of debt and government ownership using both OLS and GMM specifications and the results are robust for both approaches. The manuscript uses an instrumental variable to show that government ownership has a positive impact on higher firm performance through reducing cost of debt. Further, this paper addresses the possible issue of endogeneity.